Exploring the Lived Experiences of Students Regarding Doctoral Dissertation Writing in Iraq - Efare, Thaer Abdulsada Yaseen; Taghvaee Yazdi, Maryam; Al-Khateeb, Muna Mohammed Abbas; Emami Rizi, Kobra (Management Strategies and Engineering Sciences, 2023)
The present study aimed to explore and analyze the lived experiences of students concerning doctoral dissertation writing in Iraq. The research adopted a qualitative methodology. The statistical population in the first stage consisted of doctoral students and graduates in the field of geography in Iraq, while in the second stage, it included higher education experts such as managers, experts, and faculty members. The sample size for the first stage was determined through criterion-based purposive sampling until theoretical saturation was achieved, resulting in 10 participants. In the second stage, purposive sampling was used to select 12 participants. Data collection tools included semi-structured interviews in the first stage and the Delphi method in the second stage. Data analysis was conducted using Colaizzi's seven-step method in the first stage and content analysis with Maxqda 2020 software in the second stage. Based on the findings, the lived experiences of doctoral geography students in Iraq were categorized into four dimensions (organizational structure, student-related factors, educational and research factors, and information and communication technology), 12 main components, 34 sub-components, and 157 concepts.